Upgrading EFL teachers’ Quality through An Online Mentoring System, An Innovative In-Service Training Model: The Case of Indonesia - Zifirdaus Adnan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Many studies have been conducted in English as a Foreign Language (EFL) teacher education to improve teachers’ quality, some of these have been on mentoring teachers, with the purpose of improving teaching of English as a Foreign Language (TEFL). However, TEFL teaching is still problematic worldwide including Indonesia. Indonesian TEFL is seriously problematic because the expected levels of competencies are not adequately achieved. A major factor, teacher quality, is at issue. Even though the Government has provided models of training for its teachers, they have not been effective. This paper addresses this issue and proposes an innovative but cheaper mentoring system. This system also overcomes the shortcomings of the existing models of in-service training including its ad hoc nature, lack of practice and feedback, lack of the opportunity to upgrade poor English skills. The paper argues that the system can overcome these issues, and Indonesia is capable of running the system with its existing resources. The model could be adapted to address similar TEFL issues found elsewhere.